THE STATUS OF ADOPTED CHILDREN IN INHERITANCE ACCORDING TO THE CUSTOMARY LAW OF KAILI TRIBE IN CENTRAL SULAWESI - Aifan, Aifan; Dewi, Marini Citra (Tadulako University, 2020)
One of the goals of marriage is to achieve happiness and continue offspring. As stated in the provisions of Article 1 of Law Number 1 of 1974, that the purpose of marriage is to form a happy family and to have a close relationship with offspring. But in reality, it is not uncommon in a marriage or a family not to get offspring for various reasons, therefore it is done by taking over someone else's child which is then put into a family member as a substitute for children that cannot be obtained naturally. In this research, the juridical empirical approach method is used, while the research specification is descriptive analysis with data obtained through literature and field results. The position of adopted children as heirs of their adoptive parents and the distribution of inheritance to adopted children based on the Kaili customary law in Central Sulawesi are very important. Adopted children are often in a difficult position. Adoptive parents are always careful in the implementation of the distribution of inheritance to adopted children, the goal is to avoid inheritance disputes between their heirs, but must always adhere to the customary law adopted in the community. As for the problems that the author raises regarding 1, How is the inheritance system for adopted children in customary law? 2, What is the position of adopted children in inheriting the inheritance according to the Kaili customary law in Central Sulawesi? Although the position of adopted children is the same as that of biological children as family members of adoptive parents, in certain cases, for example, in obtaining the assets of their adoptive parents according to customary inheritance law in each region in Indonesia is not the same.